The Role of Agricultural Cooperatives in Reducing Rural Poverty: A Systematic Review of Evidence from Developing Countries - Bidari, Sandesh; Khanal, Vishnu (International Research Journal of MMC, 2026)
Rural poverty remains one of the most persistent development challenges in the world. Over 700 million people are still living below the international poverty line, and the majority of them depend on agriculture. Agricultural cooperatives have long been proposed as an institutional solution to address the structural disadvantages faced by smallholder farmers. This paper systematically reviews empirical evidence from developing countries to assess whether and how agricultural cooperatives contribute to reducing rural poverty. We reviewed 68 peer-reviewed studies published between 2000 and 2024, focusing on Sub-Saharan Africa, South Asia, Latin America, and Southeast Asia. Evidence consistently shows that cooperative membership improves household income, market access, food security, and access to credit. However, benefits are not equally distributed, and outcomes depend heavily on governance quality, member participation, and external policy support. Agricultural cooperatives are a valuable but context-dependent tool for poverty reduction. Policy interventions should focus on improving governance, promoting gender inclusion, and integrating cooperatives into broader rural development frameworks.